Meet cute - Hunting, Helena (Forever, 2019)
Kailyn Flowers was always calm, rational, and controlled - until she ended up sprawled all over Daxton Hughes, the former actor she totally crushed on as a teenager. Then she did the unthinkable: She became a mortifying fangirl in five seconds flat, which may or may not have included professing her undying love. And oddly, he didn't run away. In fact, their meet cute led to a friendship she never saw coming. Of course, she never saw his betrayal coming, either... Now Dax needs her help. As guardian to his thirteen-year-old sister, he's in way over his head. And though Kailyn hasn't forgiven Dax, she isn't heartless enough to make him fend for himself, either. Soon their friendly meetings turn into flirty dinner dates, and Kailyn can feel their chemistry is as explosive as ever. But how can she possibly let her guard again to a guy who has heartbreak written all over him?